Epidemiology and clinical record of multiple sclerosis in selected countries: a systematic review. (1st May 2014) - Niedziela, Natalia; Adamczyk-Sowa, Monika; Pierzchała, Krystyna
<x xml:space="preserve">Abstract</x> Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of the central nervous system mainly affecting young adults. The aim of this paper is to review the literature concentrating the main national MS registries in selected countries of the world. We performed a systematic review to determine the MS epidemiology reported on prevalence, incidence, environmental factors, treatment, social consequences of MS and neurological disability or progression among MS-affected people. We got the information on the high-MS prevalence in Sardinia, Sweden or Sicily and on the effects of MS treatment in United States of America, Italy or Germany. We emphasized environmental factors taking into account as MS risk factors. We concluded that there were many descriptions of MS status in particular countries, but they were often insufficiently detailed and not uniform enough to compare it. The paper indicated an importance of the MS epidemiology in the light of the healthcare or quality of life of the MS patients, but further research is needed to optimize this issue.